PENANAMAN NILAI-NILAI AJARAN ISLAM KEPADA ANAK DENGAN METODE USWATUN KHASANAH PERSPEKTIF ABDULLAH NASHIH ULWAN DALAM KITAB TARBIYATUL AULAD FIL ISLAM - Qori’ atul Munia Asri; Erwin Yudi Prahara (IAIN Ponorogo, 2020)
This article discusses Abdullah Nashih Ulwan's ideas about planting the values of Islamic teachings in children using the Uswatun Khasanah method in his book entitled Tarbiyatul Aulad fil Islam with literary study techniques as primary data, and literature related to the object of this research as secondary data. The method used is the Content Analysis approach, so that the research results are not in the form of numbers but in the form of interpretations and words. The purpose of this research is to find out how to instill the values of Islamic teachings in children in the book tarbiyatul aulad fil Islam by Abdullah Nashih Ulwan and how the uswatun khasanah method in the book tarbiyatul aulad fil Islam by Abdullah Nashih Ulwan is the value of Islamic teachings and its cultivation. It is hoped that educators will not only teach without good practice, but educators must also be good role models in all things. So that students can grow in kindness, since childhood they are familiar with noble morals. The results of this study are as follows. First, through the principle of piety, it means to fear Allah from doing what is wrong. Second, brotherhood. Third, compassion. Fourth, put others first. Fifth, the apologizer. Sixth, courage in upholding the truth in Islam. Researchers hope that the inculcation of Islamic teaching values is not only always through theory but rather to realize or practice such as the application of the uswatun khasanah method to children from the beginning of their growth until the children grow up.